A systematic review of multidisciplinary teams to reduce major amputations for patients with diabetic foot ulcers - Musuuza, Jackson; Sutherland, Bryn L.; Kurter, Suleyman; Balasubramanian, Prakash; Bartels, Christie M.; Brennan, Meghan B. (Journal of vascular surgery, 2020)
Multiple single-center studies have reported significant reductions in major amputations among patients with diabetic foot ulcers after initiation of multidisciplinary teams. The purpose of this study was to assess the association between multidisciplinary teams (ie, two or more types of clinicians working together) and the risk of major amputation and to compile descriptions of these diverse teams. We searched PubMed, Scopus, Cumulative Index to Nursing and Allied Health, and Cochrane Central Register of Controlled Trials from inception through May 24, 2019 for studies reporting the association between multidisciplinary teams and major amputation rates for patients with diabetic foot ulcers. We included original studies if ≥50% of the patients seen by the multidisciplinary team had diabetes, they included a control group, and they reported the effect of a multidisciplinary team on major amputation rates. Studies were excluded if they were non-English language, abstracts only, or unpublished. We used the five-domain Systems Engineering Initiative for Patient Safety Model to describe team composition and function and summarized changes in major amputation rates associated with multidisciplinary team care. A meta-analysis was not performed because of heterogeneity across studies, their observational designs, and the potential for uncontrolled confounding (PROSPERO No. 2017: CRD42017067915). We included 33 studies, none of which were randomized trials. Multidisciplinary team composition and functions were highly diverse. However, four elements were common across teams: teams were composed of medical and surgical disciplines; larger teams benefitted from having a “captain” and a nuclear and ancillary team member structure; clear referral pathways and care algorithms supported timely, comprehensive care; and multidisciplinary teams addressed four key tasks: glycemic control, local wound management, vascular disease, and infection. Ninety-four percent (31/33) of studies reported a reduction in major amputations after institution of a multidisciplinary team. Multidisciplinary team composition was variable but reduced major amputations in 94% of studies. Teams consistently addressed glycemic control, local wound management, vascular disease, and infection in a timely and coordinated manner to reduce major amputation for patients with diabetic foot ulcerations. Care algorithms and referral pathways were key tools to their success.